Syntactic analysis on simple sentence patterns in the ‘Talk Active’ English textbook of Merdeka Curriculum for the tenth grade at SMAN 13 Maros - Mujahidah Adawiah; Warsidi Warsidi; Sulviana Sulviana (Linguistics Initiative, 2026)
This study aims to analyze simple sentence patterns and the structure of phrases in reading texts in the Talk Active textbook for 10th grade students at SMAN 13 Maros. This study focuses on identifying syntactic sentence patterns and syntactic structures of phrases in the sentences. A total of 140 simple sentences from 14 chapters were analyzed using the classification of simple sentence patterns according to Quirk et al., (1985), phrase structure rules theory according to Bornstein (1984), and syntactic tree diagram representation according to Aarts (2001). The results showed that the most dominant sentence patterns were SVC and SVO, followed by SVOA and SVA, while complex patterns such as SVOO and SVOC rarely appeared, and the simplest pattern SV did not appear at all. Noun phrases (NPs) were dominated by Pronoun and Determiner + Noun, while verb phrases were dominated by linking verbs (Vl) with complements and transitive verbs (Vt) with objects and additional adverbials, supporting the dominance of SVC, SVO, and SVOA patterns. These findings indicate that the textbook tend to feature more descriptive sentences where sentence patterns are used to explain or identify subjects and express actions or events.